Bibliometric Analysis of Watchkeeping Onboard Ships Using Software Vosviewer - Sulistiyowati, Ely; Nurhidayati, Indah; Anita Indriyani, Kristin; Kundori, Kundori (Meteor STIP Marunda, 2025)
This article aims to conduct bibliometric research on ship crew members who carry out guard duty on ships. Research gaps in watchkeeping studies are identified and analyzed. The method used in this research is descriptive qualitative, namely by describing data visualization. The keyword chosen is "watchkeeping". Data was collected from journals that have been published in Scopus indexed journals using publish or perish (PoP) and completed using Mendeley. Next, the data is input into VOSviewer. The results obtained from the publish or Perish search found as many as 200 articles on the topic of watchkeeping published in the period from 1960 to 2023. Next, the results of data processing with VOSviewer obtained results based on keywords divided into 6 clusters. Overall, bibliometric analysis on the topic of watch keeping provides important insights into the research analyzed, which will help researchers, practitioners and policy makers understand the latest developments which are increasingly dynamic and continue to develop.